Synthesis of SnO2 Thin Coatings by Indium and Aluminum Mixed Doping using the Sol-Gel Spin-Coating Technique - Haris Munandar; Aris Doyan; Susilawati Susilawati (Jurnal Penelitian Pendidikan IPA, 2020)
This research succeeded in creating a thin layer of SnO2 and SnO2: In+Al through a synthesis process with the sol-gel spin-coating technique on a glass substrate. The manufacture of this thin layer uses the basic material SnCl2.2H2O, and the doping material InCl3.4H2O and AlCl3. This thin layer is made with variations in doping concentration, number of layers, and heating temperature. The results of the synthesis of SnO2: In+Al films show that the thin film formed is more transparent when the doping concentration and the number of layers is increased. Meanwhile, the thin layer that forms is increasingly not transparent when heated at higher temperatures